제1형 우측중도절단된 로그정규 수명 자료를 모니터링하는 누적합 관리도 - 최민재; Minjae Choi; 이재헌; Jaeheon Lee (Ŭngyong tʻonggye yŏnʼgu, 2021)
제품의 수명을 유지시키는 것은 품질관리의 주요 목표 중 하나이다. 실제 공정에서는 시간 및 비용의 문제로 인해 모든 표본의 수명을 측정할 수 없는 경우가 많이 발생하기 때문에, 대부분 중도절단된 자료를 포함시켜 표본을 구성한다. 이 논문에서는 제1형의 우측중도절단된 수명 자료가 로그정규분포를 따르는 경우, 제품 수명의 평균을 모니터링하는 두 가지 누적합 관리도 절차를 제안한다. 하나는 우도비에 기초한 누적합 관리도이고, 다른 하나는 이항분포에 기초한 누적합 관리도 절차이다. 모의실험을 통해 평균런길이를 비교하는 방법으로 제안된 두 관리도 절차의 성능을 비교하였다. 모의실험 결과, 중도절단율이 낮은 경우, 형상모수값이 작은 경우, 평균의 감소 변화량이 큰 경우에는 우도비 누적합 관리도가 더 효율적이며, 반대로 중도절단율이 높은 경우, 형상모수값이 큰 경우, 평균의 감소 변화량이 적은 경우에는 이항 누적합 관리도가 더 효율적인 것으로 나타났다. Maintaining the lifetime of a product is one of the objectives of quality control. In real processes, most samples are constructed with censored data because, in many situations, we cannot measure the lifetime of all samples due to time or cost problems. In this paper, we propose two cumulative sum (CUSUM) control charting procedures to monitor the mean of type I right-censored lognormal lifetime data. One of them is based on the likelihood ratio, and the other is based on the binomial distribution. Through simulations, we evaluate the performance of the two proposed procedures by comparing the average run length (ARL). The overall performance of the likelihood ratio CUSUM chart is better, especially this chart performs better when the censoring rate is low and the shape parameter value is small. Conversely, the binomial CUSUM chart is shown to perform better when the censoring rate is high, the shape parameter value is large, and the change in the mean is small.